Risk factors for delayed speech in children aged 1-2 years - Sabrina Tan; Irawan Mangunatmadja; Tjhin Wiguna (Indonesian Pediatric Society, 2019)
Background Speech delay is one of the most common developmental delays in children. To minimize the negative outcomes of speech delay, risk factors should be explored to help in early patient diagnosis. Objectives To assess for associations between delayed speech in children aged 1 to 2 years and possible risk factors including gender, gestational age, birth weight, asphyxia during birth, head circumference, anterior fontanelle closure, gross motor development, duration of breastfeeding, caregiver identity, number of siblings, exposure to gadgets and television, and social interaction. Methods Parents of children aged 1 to 2 years who were treated at Dr. Cipto Mangunkusumo Hospital, and Klinik Anakku, Pondok Pinang in Jakarta from January 2018 to March 2018 were interviewed. Data were processed with SPSS Statistics for Mac and analyzed by Chi-square test and logistic regression method. Results Of 126 subjects, 63 children had speech delay and 63 children had normal speech development. Multivariate analysis revealed that the significant risk factors for delayed speech were delayed gross motor development (OR 9.607; 95%CI 3.403 to 27.122; P<0.001), exclusive breastfeeding for less than 6 months (OR 3.278; 95%CI 1.244 to 8.637; P=0.016), and exposure to gadgets and television for more than 2 hours daily (OR 8.286; 95%CI 2.555 to 26.871; P<0.001). Conclusion Delayed gross motor development, exclusive breastfeeding for less than 6 months, media exposure for more than 2 hours daily, and poor social interaction are risk factors for delayed speech development in children.